Transcriptomics and metabolomics reveal the possible mechanism by which 1-methylcyclopropene regulates the postharvest senescence of Zizania latifolia. (6th January 2022) - Bata Gouda, Mohamed Hawali; Peng, Sijia; Yu, Renying; Li, Jianqi; Zhao, Guihong; Chen, Yuru; Song, Huibo; Luo, Haibo
Abstract: To understand the mechanism governing the postharvest senescence of Zizania latifolia ( Z. latifolia ), and the regulatory mechanism induced by 1-methylcyclopropene (1-MCP) during storage at 25 °C, physiobiochemical and conjoint analyses of the transcriptome and metabolome were performed. The results indicated that 1-MCP treatment engendered changes in the expression of genes and metabolites during the postharvest storage of Z. latifolia . The 1-MCP treatment maintained a good visual appearance, preserved the cell structure and membrane integrity of Z. latifolia by keeping the expression of membrane-related lipolytic enzymes (and related genes) low and the amount of phosphatidylethanolamine high. Compared to the control group, 1-MCP treatment enhanced the activities of antioxidant enzymes, resulting in a decrease of reactive oxygen species and malondialdehyde contents, and thus inhibition of oxidative damage and loss of membrane integrity. In addition, 1-MCP treatment retarded the senescence of Z. latifolia by downregulating the expression of ethylene biosynthesis-related genes and promoting upregulation of brassinosteroid insensitive 1 kinase inhibitor 1, calmodulin, glutathione reductase, jasmonate amino acid synthase, and mitogen-activated protein kinase-related genes. Moreover, 1-MCP retarded Z. latifolia senescence by inducing the activity of adenosine triphosphate (ATP) biosynthesis-related genes and metabolites. Our findings should facilitate future research on the postharvest storage of Z. latifolia, and could help delay senescence and prolong the storage time for commercial applications.